COMPARATIVE EFFICIENCY OF TEN POTATO CULTIVARS TO USE NITROGEN FROM GREEN MANURED SOIL - Trehan, S. P (Potato Journal, 2013)
Field experiment was conducted during 2003-04 on an alkaline loam deep alluvial soil (Ustochrept) of Jalandhar with ten potato cultivars and four rates of N (0, 80, 160 and 240 kg N/ha) to find their comparative efficiency to use N from green manured soil. Results showed wide variation in their efficiency. The cv. Kufri Badshah was the poor user of N from green manure whereas cv. Kufri Sutlej has the highest capacity. The increase in yield due to green manure in the absence of fertilizer N was minimum in cv. Kufri Badshah (83 q/ha) and maximum in cv. Kufri Sutlej (211 q/ha). This was due to highest increase in total uptake of N by cv. Kufri Sutlej (104 kg N/ha) and least increase in uptake of N by cv. Kufri Badshah (40 kg N/ha) due to green manure in the absence of fertilizer N.